The Expanding Blaze : How the American Revolution Ignited the World, 1775-1848 - Israel, Jonathan, 1946- (Book collections on Project MUSE., 2017)
"A major intellectual history of the American Revolution and its influence on later revolutions in Europe and the Americas, the Expanding Blaze is a sweeping history of how the American Revolution inspired revolutions throughout Europe and the Atlantic world in the eighteenth and nineteenth centuries. Jonathan Israel, one of the world's leading historians of the Enlightenment, shows how the radical ideas of American founders such as Paine, Jefferson, Franklin, Madison, and Monroe set the pattern for democratic revolutions, movements, and constitutions in France, Britain, Ireland, the Netherlands, Belgium, Poland, Greece, Canada, Haiti, Brazil, and Spanish America. The Expanding Blaze reminds us that the American Revolution was an astonishingly radical event--and that it didn't end with the transformation and independence of America. Rather, the revolution continued to reverberate in Europe and the Americas for the next three-quarters of a century. This comprehensive history of the revolution's international influence traces how American efforts to implement Radical Enlightenment ideas--including the destruction of the old regime and the promotion of democratic republicanism, self-government, and liberty--helped drive revolutions abroad, as foreign leaders explicitly followed the American example and espoused American democratic values. The first major new intellectual history of the age of democratic revolution in decades, The Expanding Blaze returns the American Revolution to its global context."--